ChemInform Abstract: Fe(III)‐Catalyzed Trityl Benzyl Ether Formation and Disproportionation Cascade Reactions to Yield Benzaldehydes. Issue 51 (December 2015) - Cheng, Maosheng; et al.,
Abstract: Depending only on temperature, FeCl3 ‐catalyzed microwave‐assisted reaction of benzyl alcohols with tritanol gives either the trityl benzyl ethers (III) or benzaldehydes (IV) in high yields.